Risk Management Based on NPV-at-Risk: A Case Study in Floating Solar Power Plant Project - Octa Untoro; Fakhrina Fahma; Wahyudi Sutopo (Jurnal Teknik Industri, 2021)
There are some unpredicted factors in floating solar power plants that can affect the investment return value. This research aimed to develop an NPV-at-risk based risk management analysis on the floating solar power plant. This research proposed six-staged solutions: communication and consultation, context assignment, risk identification, risk analysis, risk evaluation, and risk mitigation. This study took place in a floating solar power plant in Indonesia. This research showed that some unpredicted risks, such as irradiation, operation and maintenance costs, inflation, and interest rate, could contribute to the investment return. This procedural proposal could be applied in the management of the income realization based on the income projection.